ANALYSIS TIKTOK AFFILIATE CONTENT AS PURCHASE DECISION INFORMATION FOR THANKSINSOMNIA - Muti Aisya Tangguh Pratomo; Muhammad Zacky; Muhammad Tengku Ihsan; Badriyah (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The development of digital technology, particularly social media—which has become widely accessible and continues to grow rapidly—has influenced marketing patterns and consumer behavior, especially in determining purchasing decisions. This study aims to measure the effectiveness of affiliate content on the TikTok app in influencing purchasing decisions for products from the Thanksinsomnia brand. The research employed a descriptive quantitative approach using a Likert scale through the distribution of questionnaires to 31 respondents. The results indicate that 45.2% of respondents were interested in purchasing Thanksinsomnia products after viewing TikTok affiliate content, 43.3% felt confident about the products after watching such content, and 51.6% stated that they had purchased Thanksinsomnia products. Most respondents perceived affiliate content as providing clear product information, attractive visuals, and trustworthy reviews from affiliates. Therefore, TikTok Affiliate can be utilized as a digital promotional medium capable of increasing consumer interest while also influencing the purchasing decision-making process for Thanksinsomnia products.